2022
DOI: 10.3390/nu14193916
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Glycemic and Insulinemic Response by a Brewer’s Spent Grain Extract-Based Food Supplement in Subjects with Slightly Impaired Glucose Tolerance: A Monocentric, Randomized, Cross-Over, Double-Blind, Placebo-Controlled Clinical Trial

Abstract: Dietary fiber exerts beneficial effects on human health reducing the risk factors of metabolic related diseases such as hyperglycemia, insulin resistance, and hypercholesterolemia. The aim of this study is to demonstrate the efficacy of a food supplement based on brewer’s spent grain (BSG) extract in the reduction of postprandial glycemia and insulinemia in normoglycemic subjects. BSG was chemically characterized, revealing the presence of resistant starch (14.64 g/100 g), arabinoxylans (7.50 g/100 g), β-gluca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…These records are updated daily by these physicians, who upload all data concerning their outpatient activities. Of note, the territorial distribution of individuals assisted by these primary physicians is similar to the one of the city population recorded by the Italian National Institute of Statistics (ISTAT), with no differences in terms of geographic area or aggregation by age [ 22 , 23 ]. The COMEGEN database collects diagnoses according to the International Classification of Diseases 10 ( ICD-X ) recorded by primary care providers, also using standardized codes for all prescribed diagnostic assessments.…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…These records are updated daily by these physicians, who upload all data concerning their outpatient activities. Of note, the territorial distribution of individuals assisted by these primary physicians is similar to the one of the city population recorded by the Italian National Institute of Statistics (ISTAT), with no differences in terms of geographic area or aggregation by age [ 22 , 23 ]. The COMEGEN database collects diagnoses according to the International Classification of Diseases 10 ( ICD-X ) recorded by primary care providers, also using standardized codes for all prescribed diagnostic assessments.…”
Section: Methodsmentioning
confidence: 76%
“…Additionally, the database includes information on vital parameters, weight, height, BMI, waist circumference, chronic conditions, medical visits, hospitalizations, emergency department visits, prescription drug dispensations, testing and vaccinations (including for COVID-19), date, and cause of death. All these precious pieces of information allow for real-time provision of data related to the management of patients in terms of processes and outcomes, use of drugs, diagnostic investigations, and the complexity and comorbidities of the assisted population [ 23 ]. Moreover, an accurate evaluation of person-time is crucial for calculating incidence rates and the COMEGEN allows such assessment, by specifying when each individual has been entered in the database and started contributing data to the cohort, as well as the dates of death, end of follow-up, and end of observation.…”
Section: Methodsmentioning
confidence: 99%
“…This implies that the presence of other compounds within BSG may also contribute to the decrease in PPGR observed. In a prior study by Ullah, et al [ 36 ], the consumption of BSG extract-based breadsticks with matched ACHO showed an improvement in PPGR at 90 and 120 min compared to the consumption of plain breadsticks in individuals with impaired glucose tolerance. As a high-fibre food by-product, BSG-containing biscuits showed a significantly higher total dietary fibre content [ 18 ] and this dietary fibre is able to increase the viscosity of gastric contents and slow down gastric emptying, leading to a delayed and reduced glucose absorption [ 37 ].…”
Section: Discussionmentioning
confidence: 95%
“…It is a functional staple food because it has better functions, including controlling postprandial blood glucose and insulin and fewer negative factors such as the early onset of hunger. In recent years, brewers’ spent grain extracts, including resistant starch, arabinoxylan, beta-glucan and other soluble fiber, have been shown to lower blood glucose and insulin to normal levels [ 26 ]. These components may also contribute to improved glycemic control by YPP.…”
Section: Discussionmentioning
confidence: 99%